HUBUNGAN BIAYA MATERIAL KAPAL TERHADAP LABA OPERASI - Denny Najoan; Yosi Pahala; KI Yunandyan (Institut Transportasi dan Logistik Trisakti, 2016)
PT. Pertamina Trans Kontinental is one of PT Pertamina subsidiary focused on chartered ships in short and long terms for shipping supply, anchor handling, tugs offshore oil company, and gas for industry. The purpose of the research is to analyse the ship material’s cost with the profit of MT Patra Tanker I PT. Pertamina Trans Kontinental from 2010 to 2012. The researcher is using quantitative method, field and library research. The result shows that the ship material’s cost is still unstable from year to year which affects the profit of the ship and the company.